1991
DOI: 10.1152/jn.1991.66.5.1716
|View full text |Cite
|
Sign up to set email alerts
|

Superior colliculus neurons mediate the dynamic characteristics of saccades

Abstract: 1. The locus of activity within the superior colliculus (SC) is related to the desired displacement of the eye. Current hypotheses suggest that the location of this locus of activity determines the amplitude of the saccade and that the level of activity at this locus determines eye velocity. We present evidence that suggests that, although the locus determines the amplitude of the saccade, the level of activity in the colliculus encodes dynamic motor error (the difference between desired and current eye displa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
136
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(148 citation statements)
references
References 0 publications
11
136
1
Order By: Relevance
“…On the one hand, it may suggest that the level of perisaccadic perceptual compression varies with the strength of the corresponding saccadic motor command: saccadic peak velocities correlate with average firing rates of burst neurons recorded in the superior colliculi (Waitzman et al, 1991) and the pontomedullary reticular formation (Van Gisbergen et al, 1981). The superior colliculi and downstream structures provide an important source of reafferent signals that are fed back to frontal and parietal oculomotor areas via thalamic relay nuclei (Buttner-Ennever and Henn, 1976;Sommer and Wurtz, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, it may suggest that the level of perisaccadic perceptual compression varies with the strength of the corresponding saccadic motor command: saccadic peak velocities correlate with average firing rates of burst neurons recorded in the superior colliculi (Waitzman et al, 1991) and the pontomedullary reticular formation (Van Gisbergen et al, 1981). The superior colliculi and downstream structures provide an important source of reafferent signals that are fed back to frontal and parietal oculomotor areas via thalamic relay nuclei (Buttner-Ennever and Henn, 1976;Sommer and Wurtz, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Investigations of saccade dynamics during SC stimulation and recordings have suggested that the SC does influence velocity (Waitzman et al, 1991;Guitton, 1992;Van Opstal et al, 1995;Munoz et al, 1996). Head-restrained studies that dissociated target location from gaze kinematics by varying initial eye position (Sparks and Mays, 1980) or perturbing eye muscles have suggested that SC neurons correlate best to the former, rather than the latter.…”
Section: Target Versus Gaze Movement Codingmentioning
confidence: 99%
“…20), which repre- sents where the eye should go (Robinson 1975;van Gisbergen et al 1981;JĂŒrgens et al 1981;Scudder 1988;van Gisbergen and van Opstal 1989;Waitzman et al 1991). E d needs to be a sustained signal: it not only represents where to go but also drives the saccade.…”
Section: Spatial Aspects Of Saccadesmentioning
confidence: 99%